Mental representations of 12 year-old children about boiling and evaporation: A probabilistic association with convergent and divergent thinking - Tsikalas, Themistocles; Stamovlasis, Dimitrios; Papageorgiou, George (Preschool and Primary Education, 2014)
Students’ understanding of physical phenomena is determined by their relevant representations, which are very crucial for science education. Since these representations are often incompatible with the scientific view, their functional role in the learning processes has been the main interest of a plethora of research work over the last decades. In the present research students’ representations for boiling and evaporation are investigated and an attempt is made to correlate them with two cognitive variables, which have been shown to be involved in mental processes of learning science, namely convergent and divergent thinking. The study took place with the participation of 375 sixth-grade elementary school pupils (aged 11-12). Methodologically the ordinal logistic regression was implemented to correlate the categorical-type dependent variable with scale-type independent predictors. The results show that both convergent and divergent thinking are significantly associated with pupils’ sufficient responses. Interpretation of the results and implications for science education are discussed.